Penerapan Metode MABAC dalam Sistem Pendukung Keputusan Rekomendasi Aplikasi Pemesanan Hotel Terbaik - Rima Tamara Aldisa (Journal of Information System Research (JOSH), 2022)
People's needs for ordering applications are very popular in today's digital age because they can make it easier for people. One of the booking applications is a hotel booking application which aims to prevent people from having to queue to make hotel reservations and can see many hotel choices and other holiday needs in one application. Many hotel booking applications are available on the Playstore and Appstore, making people hesitant to determine the right application for making hotel reservations. The Decision Support System is applied in this study as a system for recommending the best hotel booking application. In determining the best hotel booking application recommendation, it must meet criteria such as Application Features, Payment Options, Application Ratings, Number of Users and Storage Capacity. Therefore, a Decision Support System (DSS) is needed in solving existing problems by applying the MABAC (Multi-Attributive Border Approximation area Comparison) method which can generate preference values ​​from the first ranked alternative. So that the recommendation for the best hotel booking application lies in the alternative H8 on behalf of Traveloka with a value of 0.51283.